Афориcтика Віри Вовк як відображення світогляду авторки - Григорчук, Ю. (Лексикографічний бюлетень, 2012)
The article is devoted to the analysis of the aphoristic language in Wira Wowk’s prosaic works. There three groups of the aphorisms, revealed in her belletristic texts: philosophical, religious-Christian and the anthropological. The analysis of those ones permits to outline the Wira Wowk artistic thinking originality and the mental and ethical values.